2015
DOI: 10.1371/journal.pone.0129742
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impact of Skeletal Muscle Loss after Systemic Chemotherapy in Patients with Unresectable Colorectal Cancer

Abstract: BackgroundSkeletal muscle depletion (sarcopenia) is closely associated with limited physical ability and high mortality. This study evaluated the prognostic significance of skeletal muscle status before and after chemotherapy in patients with unresectable colorectal cancer (CRC).MethodsWe conducted a retrospective analysis of 215 consecutive patients with unresectable CRC who underwent systemic chemotherapy. Skeletal muscle cross-sectional area was measured by computed tomography. We evaluated the prognostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 23 publications
(20 reference statements)
7
99
3
1
Order By: Relevance
“…Previous studies have reported that skeletal muscle mass at baseline is not associated with survival outcome in mCRC patients receiving front-line chemotherapy whereas skeletal muscle loss during chemotherapy clearly predicts long-term outcome [9][10][11]. These results contrast with our data.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that skeletal muscle mass at baseline is not associated with survival outcome in mCRC patients receiving front-line chemotherapy whereas skeletal muscle loss during chemotherapy clearly predicts long-term outcome [9][10][11]. These results contrast with our data.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have demonstrated that loss of skeletal muscle is a significant risk factor for short-and long-term outcomes after surgery for CRC [7,8]. In addition, It has been reported that changes in skeletal muscle mass during chemotherapy, but not changes before chemotherapy, is significantly associated with clinical outcome in mCRC patients treated with front-line chemotherapy [9][10][11]. However, the significance of alterations in skeletal muscle among patients with pretreatment refractory cancer, in whom cancer cachexia is a more common problem, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, several studies have proposed that cancer therapy may have direct effects on skeletal muscle or may cause a pro-inflammatory state that leads to proteolysis. Recent work highlights significant skeletal muscle loss during the course of chemotherapy (11, 37, 38). …”
Section: Discussionmentioning
confidence: 99%
“…Adequate muscle mass, and possibly greater muscle mass than noncancer patients, has been shown to be a strong determinant of overall mortality in several studies of cancer patients. (28-39) Studies of CRC patients with advanced disease found that muscle wasting was associated with worse recurrence-free and/or overall survival(40) as well as poor response to chemotherapy. (41) Persons with low muscle mass experience elevated low-grade systemic inflammation,(42) and altered mitochondrial function,(43, 44) both of which may influence cancer progression .…”
Section: Discussionmentioning
confidence: 99%